Break the Borders. The Struggles of Migrant Organizations and the Emergence of an Anti-racist Claim (1998-2018, Santiago) (Palimpsesto, 2021)
Since the mid-nineties, the Latin American and Caribbean migration that has arrived in the country has sought to integrate into social life in our cities. In Santiago, migrant communities had to face a series of social violence and exclusion processes based on a series of racialization and de-citizenization practices, constituting a social heterogeneity of support networks and social organizations. This article affirms the need to question certain analytical frameworks in order to understand the agency of migrants in the face of racialization processes and contribute in this sense by exploring the organizational and demands dynamics of migrant organizations. In this context, this article explores from a sociohistorical perspective a line of development of these organizations that went from being spaces of mutual support for their social insertion led by peruvian political refugees, to the development of social and sectoral organizations, maturing politically and organizationally in articulation processes that have come to have a national scale and links with other social movements. Process in which they have raised a series of claims to end the exclusions and racism faced by their communities, framing their struggles in a discourse on human rights that extends its recognition to all inhabitants regardless of nationality or skin color, having in his agency a democratizing role in Chilean society.
Keywords: Migrant organizations; anti-racism; migrant struggles; collective agency; claims frameworks